Analisis Perpajakan terhadap Insentif PPH Final atas Kepatuhan Wajib Pajak UMKM di Pamekasan - Fitrianti, Rani Nur; Rahayu, Runik Puji; Rohmaniyah, Rohmaniyah; Alfian, Nurul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The aim of this research is to find out how understanding of taxation and final PPh incentives affects taxpayer compliance. The research method uses a quantitative descriptive approach. The population in this research is corporate MSME taxpayers who take advantage of the final income tax incentives. The sampling technique used is non-probability sampling, namely purposive sampling. The type of data used in this research is quantitative data with a descriptive approach, namely in the form of primary data and secondary data. Based on the previous results and discussion, it can be concluded that: Results Based on the first hypothesis test (H1) in this study, the tax understanding variable shows a significant value smaller than 0.05, namely 0.000 and the second hypothesis test (H2) in this study, the tax incentive variable final income shows a significant value smaller than 0.05, namely 0.000.